Internalizing the Value of Mutual Cooperation in Ananda Kindergarten in Pulau Tengah Village - Ade Candra Gustia (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
This study aims to internalize the value of mutual cooperation in Ananda PAUD students in Pulau Tengah Village. This is due to the influence of modernization which forms an individualistic attitude, making it difficult to cooperate, take responsibility and help each other. The research method used is qualitative research using a naturalistic inquiry approach. Informants in this study used purposive sampling. Data collection was carried out through observation, interviews, and documentation studies. Data analysis using triangulation of data sources, with stages of data collection, data reduction, data presentation, conclusions, and data verification. The results of the study indicate that the process of internalizing the value of mutual cooperation in students is carried out in several stages, the first stage of transformation is carried out through oral communication, written communication, and listening and reading. second, the stage of value transactions through two-way communication, and the third stage of transinternalization is carried out by collaboration, habituation, and exemplary behavior. The process of internalizing the value of mutual cooperation in students from an early age can cultivate and preserve the values and meaning of mutual cooperation, such as cooperation, solidarity, responsibility, togetherness, concern, and unity. This study is expected to contribute to the importance of maintaining and preserving the values of cooperation from an early age so that they are not lost in the current era of modernization.